(untitled) (Revista Internacional de Formação de Professores, 2018)
This article indicates the various meanings teacher training has been receiving in face-to-face Pedagogy courses, through the analysis of 144 curricular matrixes undertaken by GEPEFE-FEUSP research group. It analyses aspects of the expansion of these courses from 1996 onwards, focusing on the importance of practical and theoretical knowledge to the teacher training. As a conclusion, we noticed fragmentation and blurred definitions when concerning to specific knowledge, aspect that correlates to both the expansion policies adopted and to the Pedagogical DCNs.